The Effect of Leverage, Profitability and The Audit Committee on Audit Delay With Company Size as a Moderated Variables - Kristanti, Corry; Mulya, Hadri (Dinasti Publisher, 2021)
The purpose of this study is to analyze the influence of leverage, profitability and audit committee on audit delays in property and real estate building companies listed on the Indonesia Stock Exchange for the period 2014-2018. With 29 samples. The research methodology is by descriptive quantitative method by using panel data that combines time series and cross-sectional, using secondary data obtained through the Indonesia Stock Exchange website and the company’s website. This research sampling technique uses purposive sampling. The data analysis used is a logistic regression model. The results of this study show that partial variable leverage has a negative and significant influence on audit delays. Variable profitability has a positive and significant effect on audit delays. The audit committee has a positive and significant effect on audit delays. The size of the company is able to moderate significantly positive leverage against audit delays. The Company’s measure is able to negatively moderate profitability and the audit committee against audit delays.